Toxoplasmosis in non‐cardiac solid organ transplant recipients: A case series and review of literature. Issue 1 (12th December 2019) - Ramanan, Poornima; Scherger, Sias; Benamu, Esther; Bajrovic, Valida; Jackson, Whitney; Hage, Chadi A.; Hakki, Morgan; Baddley, John W.; Abidi, Maheen Z.
Abstract: The risk of toxoplasmosis in high‐risk cardiac transplant recipients is well recognized prompting universal donor and candidate screening with administration of targeted post‐transplant chemoprophylaxis in high‐risk (D+/R−) cardiac transplant patients. In contrast, until recently, there have been neither well‐defined recommendations nor consensus regarding toxoplasmosis preventive strategies among non‐cardiac solid organ transplant recipients. We report 3 cases of post‐transplant toxoplasmosis in non‐cardiac transplant recipients (one lung and two liver); all 3 infections presumed to be donor‐derived. Not surprisingly, pre‐transplant Toxoplasma serology was negative in all the patients. None of the patients were on trimethoprim‐sulfamethoxazole (TMP‐SMX) prophylaxis at the time of diagnosis of toxoplasmosis. The median time from transplant to onset of infection was 90 days (range: 30‐120 days). Clinical presentations included cerebral (n = 1) and disseminated infections (n = 2). Two of the 3 patients, both with disseminated infection died (mortality ~ 67%).